Who Plans? Who Participates? Critically Examining Mentoring Programs - Catherine A. Hansman (Adult Education Research Conference, 2001)
The purpose of this paper is to explore the literature concerning formal mentoring programs from a socialist feminist perspective that allows an examination of power issues and the intersection of gender, race, class, and sexual orientation within mentoring relationships.